(3GdNWGHI GdYQHjI h af GdEdbGA (B/s - (3CTQa, eMeO ehSi s ((3GdbGgQI (B:s (3ecJHI GdNGfLj HGdbGgQI ,s, 1978)
(3GdNWGHI h fTCJgG af GdNWGHIh CfhGYgG (B.(3GdfKQ GdLGgdj eejRGJg aj GdYUQ GdLGgdjs
Keywords: (3GdNWHIs; (3GdfKQ GdLGgdjs